Media Syi’ar Islam Interaktif Berbasis Animasi 3D di Masa Pandemi - Tarigan, Muhammad Fikriansyah (TIN: Terapan Informatika Nusantara, 2022)
Along with the rise of the Covid-19 outbreak, it is increasingly difficult for humans to convey the symbols of Islam, especially the scholars and preachers. One way to overcome limitations in conveying Islamic symbols is by utilizing interactive media based on 3D animation. The interactive media built can provide information about Islamic symbols with the theme of juvenile delinquency aimed at the general public, especially teenagers. This 3D animation is designed using Blender software. The manufacturing process starts from determining story ideas, making storyboards, object modeling, giving textures, moving animations, dams to rendering. The final result of this animation is an interactive video equipped with background music and sound from the object. Interactive Islamic syi'ar media based on 3D animation during this pandemic as education to overcome juvenile delinquency in the community, so that this media can be useful and useful for teenagers